Coherent noise suppression in digital holographic microscopy based on label-free deep learning - Wu, Ji; Tang, Ju; Zhang, Jiawei; Di, Jianglei (Frontiers in Physics, 2022)
Deep learning techniques can be introduced into digital holography to suppress phase noise. It is often necessary to first make a dataset of noisy and noise-free phase images to train the network. However, noise-free images are often difficult to obtain in practical holographic applications. Here we propose a label-free training algorithms based on self-supervised learning. A dilated blind spot network (DBSN) is built to learn from the real noisy phase images and a noise level function network (NLFN) to estimate a noise level function. Then they are trained together via maximizing the constrained negative log-likelihood and Bayes’ rule to generate a denoising phase image. The experimental results demonstrate that our method outperforms standard smoothing algorithms in accurately reconstructing the true phase image in digital holographic microscopy.